Bacteremia due to Roseomonas gilardi: A case report - Dandamudi, Radha Rani; Shah, Kinjal; Boyela, Pavan Kumar; Sravanthi, C H; Nayani, Swathi (Indian Journal of Case Reports, 2024)
Implantation and the use of long-term central venous catheters are associated with complications like bacteremia. Contamination from the skin during handling is the most common source of the organisms causing these infections. Rarely, environmental organisms may cause these infections. Roseomonas gilardii is a rare opportunistic pathogen that can cause bacteremia in immunocompromised patients on long-term central venous catheters. We report the case of a 57-year-old woman diagnosed with acute myeloid leukemia who presented with fever and febrile neutropenia. The patient was diagnosed with R. gilardii bacteremia probably from peripherally inserted central catheter line infection.